Microbial enzymes as powerful natural anti-biofilm candidates - Lamiaa A. Al-Madboly; Asmaa Aboulmagd; Mohamed Abd El-Salam; Ivan Kushkevych; Rasha M. El-Morsi (Microbial Cell Factories)
Abstract Bacterial biofilms pose significant challenges, from healthcare-associated infections to biofouling in industrial systems, resulting in significant health impacts and financial losses globally. Classic antimicrobial methods often fail to eradicate sessile microbial communities within biofilms, requiring innovative approaches. This review explores the structure, formation, and role of biofilms, highlighting the critical importance of exopolysaccharides in biofilm stability and resistance mechanisms. We emphasize the potential of microbial enzymatic approaches, particularly focusing on glycosidases, proteases, and deoxyribonucleases, which can disrupt biofilm matrices effectively. We also delve into the importance of enzymes such as cellobiose dehydrogenase, which disrupts biofilms by degrading polysaccharides. This enzyme is mainly sourced from Aspergillus niger and Sclerotium rolfsii, with optimized production strategies enhancing its efficacy. Additionally, we explore levan hydrolase, alginate lyase, α-amylase, protease, and lysostaphin as potent antibiofilm agents, discussing their microbial origins and production optimization strategies. These enzymes offer promising avenues for combating biofilm-related challenges in healthcare, environmental, and industrial settings. Ultimately, enzymatic strategies present environmentally friendly solutions with high potential for biofilm management and infection control.